Different modes of proton translocation by sensory rhodopsin I. - Haupts, U (1996)
The membrane-bound complex between sensory rhodopsin I (SRI) and its transducer HtrI forms the functional photoreceptor unit that allows transmission of light signals to the flagellar motor. Although being a photosensor, SRI, the mutant SRI-D76N and the HtrI-SRI complex can transport protons, as we demonstrate by using the sensitive and ion-specific black lipid membrane technique. SRI sustains an orange light-driven (one-photon-driven) outward proton transport which is enhanced by additional blue light (two-photon-driven). The vectoriality of the two-photon-driven transport could be reversed at neutral pH from the outward to the inward direction by switching the cut-off wavelength of the long wavelength light from 550 to 630 nm. The cut-off wavelength determining the reversal point decreases with decreasing pH. The currents could be enhanced by azide. A two-photon-driven inward proton transport by SRI-D76N (catalyzed by azide) and by the complex HtrI-SRI is demonstrated. The influence of pH and azide concentration on the rise and decay kinetics of the SRI380 intermediate is analyzed. The different modes of proton translocation of the SRI species are discussed on the basis of a general model of proton translocation of retinal proteins and in the context of signal transduction.